Online Implementation of Inequality Constraints Monitoring in Dynamical Systems - Nadia Zanzouri; Ramzi Ben Messaoud; Mekki Ksouri (Journal of Control Science and Engineering)
This paper deals with fault detection in dynamical systems where the state variables evolutions are constrained by inequality constraints. The latter corresponds either to physical limitations or to safety specification. Two classical residual generation approaches are studied, namely, parity space and unknown input observer approaches, and are extended to monitor the inequality constraints. A practical implementation on a real process is performed and permits to validate the relevance of the proposed methods.